Detection and a possible link between parvovirus B19 and thyroid cancer. Issue 6 (May 2017) - Etemadi, Ashkan; Mostafaei, Shayan; Yari, Kheirollah; Ghasemi, Amir; Minaei Chenar, Hamzeh; Moghoofei, Mohsen
Human parvovirus B19 (B19) is a small, non-enveloped virus and belongs to Parvoviridae family. B19 persists in many tissues such as thyroid tissue and even thyroid cancer. The main aim of this study was to determine the presence of B19, its association with increased inflammation in thyroid tissue, and thus its possible role in thyroid cancer progression. Studies have shown that virus replication in non-permissive tissue leads to overexpression of non-structural protein and results in upregulation of proinflammatory cytokines such as interleukin 6 and tumor necrosis factor alpha. A total of 36 paraffin-embedded thyroid specimens and serum were collected from patients and 12 samples were used as control. Various methods were employed, including polymerase chain reaction, real-time polymerase chain reaction, and enzyme-linked immunosorbent assay. The results have shown the presence of B19 DNA in 31 of 36 samples (86.11%). Almost in all samples, the levels of non-structural protein 1, nuclear factor kappa B, tumor necrosis factor alpha, and interleukin 6 were simultaneously high. The presence of parvovirus B19 has a significant positive correlation with nuclear factor kappa B, tumor necrosis factor alpha, and interleukin 6 levels. This study suggests that B19 infection may play an important role in tumorigenesis and thyroid cancer development via the inflammatory mechanisms.